The good secret virtues extracted from the apparent biography, a study in historical criticism - Iman Farhan Kadhim, Asst. Prof. (lark, 2025)
The books, biographies, and historical writings that addressed the figure of Sultan Baybars have been numerous and diverse. This is due to his status as a sultan destined for many significant victories and immortalized in history as a triumphant and powerful leader. Many writers exaggerated in portraying him as a legendary, almost mythical figure because of his victories over the Mongols and the Crusaders and his triumphs over his enemies. However, only a few historians approached the personality of Baybars with neutrality and without exaggeration, chief among them was Shafiʿ ibn ʿAli, who stripped away the glorified image and halos surrounding the Sultan and presented the facts without alteration or distortion. This approach is essential for researchers and historians alike. Several factors enabled Shafiʿ ibn ʿAli to write with such fairness and objectivity. One key factor was that he wrote his account after the death of Sultan Baybars, thereby removing the pressure and fear of the Sultan’s anger or that of his court. Moreover, many authors who wrote about prominent figures were motivated by material gain or the desire to win the favor of their subjects. Shafiʿ ibn ʿAli was not bound by such motives, allowing him and his family to write freely and without flattery. Here, the role of the researcher emerges in highlighting these texts and demonstrating their significance, particularly since they preserved for us an important period of Islamic history, both due to its long duration and vast geographical span. Additionally, Shafiʿ ibn ʿAli focused on events that had been largely neglected by other historians, which is why he referred to them as “secret” virtues.